Research Progress on Human Ovarian Aging Using Non-Human Primates as Laboratory Animals - XIAO Wenxian; LÜ Longbao (Shiyan dongwu yu bijiao yixue)
The ovary has two main functions: folliculogenesis and hormone secretion, both of which are closely related to female fertility. Ovarian aging is characterized by morphological changes, a reduction in follicle numbers, and fluctuations in hormone levels. It not only leads to a decline in female fertility, but is also considered to be a key driver of multi-organ aging. In addition, the disruption of sex hormone secretion associated with ovarian aging can lead to the occurrence of related diseases and symptoms, such as cardiovascular diseases, sleep disorders, and hot flashes. Due to the influence of social pressures and personal career planning, many modern women are increasingly postponing childbearing. However, ovarian aging does not slow down with advancing age. As a result, many women face issues such as infertility when they are ready to have children, having missed their optimal childbearing age. This leads to growing interest in research on delaying ovarian aging. Non-human primates share the closest evolutionary relationship with humans, with a genomic sequence identity of 93%, which grants them unparalleled advantages over other model animals in studies on physiological metabolism, reproductive endocrinology, and developmental aging. Findings obtained in non-human primates are also more reliably translatable to human medical research. This study begins by discussing the current state of ovarian aging research and treatment strategies, highlighting the advantages of non-human primates as laboratory animals for ovarian aging research. It then reviews research progress in areas such as reproductive endocrine hormone levels, ovarian morphology and function, and other physiological changes associated with ovarian aging. Furthermore, it summarizes existing challenges and future research directions, aiming to provide valuable insights for researchers.